Development of the Russian socio-economic system: challenges and prospects - Alekseenko M. V., Golub I. I., Verenikina A. O., Terioshina V. V., Medvedeva N. V., Shpak A. S., Krutova O. V., Kashirin A. I., Poletaev I. V., Kruglov V. N., Tiutin D. V., Kruglov V. N., Petrov A. M. (Development of the Russian socio-economic system: challenges and prospects, 2024)
the chapter analyzes the key trends of digital transformation based on factors determining the development of digital technologies. Digital transformation implies the integration of digital technologies into all aspects of an organization's activities, including operations, processes, and business models. Based on the classification of influencing factors, the main directions of digital transformation are defined in the form of four directions. Also, problems arising during digital transformation are considered, and its advantages are presented.
Keywords: цифровизация; цифровые технологии; digitalization; цифровая трансформация; digital transformation; digital technologies